Globalisasi, Migrasi, Dan Keamanan Nasional Malaysia: Satu Tinjauan Literatur - Firdaus Misran; Aini Fatihah Roslam (Jurnal Studi Diplomasi dan Keamanan, 2015)
Migration issue is not merely draw attention to Malaysia but also to every sovereign state(s) in today’s globalized world. The Issue of migration has been regard as prime subject that able to threat national security and vis-à-vis state relations. Thus with the understanding of research main terminology such as globalization, migration and national security, the study is set to explore factors that lies toward the mobilization of foreign migrants to Malaysia, while becoming the actual threat to state national security. The study been conducted in qualitative method via content analysis approach. Secondary data were retrieved and collected from printed and also reliable online sources that fit for academic reference. The preliminary result indicate that globalization encourage the mobilization of illegal foreign migrants that later posit an actual threat to Malaysian national security.